Effects of Shots Under The Basket Shoot and Eye-Hand Coordination on Shot Results in Basketball Extracurricular Students at MAN 1 Semarang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The research was motivated by the shot technique, which was conducted by students who took extracurricular activities less than the maximum. The purpose of this study was to analyze the effect of clear and bank shoot on the results of shooting in basketball, to analyze the effect of high and low eye-hand coordination on the results of shots in basketball, the interaction between clear and bank shoot with eye-hand coordination to the results of shooting in the basketball game on extracurricular students of Public Madrasah Aliyah (MAN) 1 Semarang. The method used in this study is to experiment with 2x2 factorial design. The population in this study amounted to 28 male students. Sampling in this study uses purposive sampling technique. The sample used 24 male extracurricular students MAN 1 Semarang, from the two-way Anova test that all three hypotheses were accepted. There is a significant difference in effect between the clear shoot and the bank shoot technique on basketball shots